Reproduksi Ketimpangan Sosial dalam Pendidikan Berdasarkan Teori Pierre Bourdieu dalam Perspektif Sosiologi Kritis - ariska, Iis; Catherine Felisha Pramadita; Inasyah Mutia Putri; Vieronica Varbi Sununianti; Istiqomah Istiqomah; Deni Aries Kurniawan (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This study examines the reproduction of social inequality in education through the theoretical framework of Pierre Bourdieu within a critical sociology perspective. The background of this research is rooted in the persistent gap in educational access, participation, and achievement among students from different social classes, which indicates that education does not always function as a tool for social mobility. The objective of this study is to analyze how mechanisms such as habitus, cultural capital, social capital, and the educational field contribute to sustaining inequality. This research employs a qualitative descriptive approach, with data collected through in-depth interviews, observations, and document analysis within an educational setting characterized by diverse socio-economic backgrounds. The findings reveal that students from higher socio-economic backgrounds tend to possess dominant cultural capital and habitus that align with institutional expectations, giving them a significant advantage in academic achievement. Conversely, students from lower socio-economic backgrounds face structural and symbolic barriers that limit their opportunities. The study also finds that educational practices, including teaching methods and evaluation systems, implicitly favor certain groups, thereby reinforcing inequality. The implications of this research highlight the need for more inclusive educational policies and practices that recognize diverse forms of capital and promote equal opportunities for all students. Ultimately, this study contributes to a deeper understanding of how education functions as a site of social reproduction rather than merely a neutral institution.